Performance of a liquid cooling‐based battery thermal management system with a composite phase change material. (29th February 2020) - Zhao, Yanqi; Li, Qi; Zou, Boyang; Zhang, Tongtong; Jin, Lu; Qiao, Geng; Nie, Binjian; Huang, Yun; Ding, Yulong
Summary: This article reports a recent study on a liquid cooling‐based battery thermal management system (BTMS) with a composite phase change material (CPCM). Both copper foam and expanded graphite were considered as the structural materials for the CPCM. The thermal behaviour of a lithium‐ion battery was experimental investigated first under different charge/discharge rates. A two‐dimensional model was then developed to examine the performance of the BTMS. For the copper foam‐based CPCM modelling, an enthalpy‐porosity approach was applied. The numerical modelling aimed to study the impacts of CPCM types and inlet velocity of heat transfer fluid on both the maximum battery temperature and temperature distribution under different current rates. Dimensional analyses of the results were performed, leading to the establishment of relationships of the Nusselt numbers and dimensionless temperature against the Fourier and Stefan numbers. Abstract : Accurate heat generation rate of lithium‐ion batteries against time was achieved experimentally. The data was then input into a two‐dimensional model as the heat source. Thermal management performance of copper foam‐based composite phase change material (CPCM) and expanded graphite (EG)‐based CPCM has been compared. It was concluded that the EG‐based CPCM has a better cooling ability than the copper foam‐based CPCM. It was also revealed that the CPCM based cooling is sufficient for battery operation under a low current rate in a single charge/discharge cycle. Liquid cooling must be used for a continuous operation and under a high current rate. Dimensional analysis of the numerical results was further performed. The results revealed that heat conduction dominated the heat transfer between the CPCM and the heat transfer fluid.